Pengembangan Model Permainan Basgedor Untuk Pembelajaran Passing Dan Shooting Bola Basket Pada Siswa Kelas VII SMP - Laela Munawaroh; Andry Akhiruyanto; Mugiyo Hartono; Dwi Gansar Santi Wijayanti (Universitas Negeri Semarang, 2024)
The background in this study is the lack of development of the basketball learning process in schools. The purpose of this research is to produce a Basgedor game model in basketball learning. The research method used is development research that refers to Brog & Gall, namely: (1) Needs analysis. (2) Initial product development planning (3) Initial product manufacturing, (4) Small group trial, (5) Initial product revision (6) Large group trial, (7) Final product. Based on the results of the small group trial, the evaluation data obtained from the PE and learning experts were 89.23% (good), and the overall average results of student responses in the small group trial obtained a percentage of 88.83% (good). The results of the large group trial obtained evaluation data from PE experts and learning experts, namely 95% (very good), and the overall average results of student responses in the large group trial obtained a percentage of 95% (very good). Based on the results of the development of the learning model, it can be concluded: (1) The Basgedor game model that has been produced in this study is feasible and can be used for grade VII junior high school students. (2) The Basgedor game model can be an effective and fun alternative model of learning PE for junior high school students